43 Dressler's syndrome post left atrial appendage occlusion: a rare diagnoses resurfaces. (6th October 2022) - O'Regan, J; O'Sullivan, C
Abstract : Abstract: Three weeks post-procedure, an 85 year old male developed a new pericardial effusion. Infectious and malignant causes were excluded. Cytology demonstrated mixed inflammatory cells and a diagnosis of DS was made. One-month and six-month clinical review with trans-oesophageal echocardiogram (TOE) showed sustained resolution of the pericardial effusion. DS is a rarely reported complication of LAAO. Background: Dressler's Syndrome also known as post myocardial infarction syndrome is a secondary pericarditis that can occur after cardiac myocyte damage. Such damage can occur after a myocardial infarction or routine endovascular surgery. It can present with or without pericardial effusion. DS has a significantly declining incidence due to the improved and more aggressive revascularisation techniques currently in use. This case was an iatrogenic cause via an intracardiac intervention. This intervention was a left atrial appendage occlusion (LAAO) with the AMPLATZER amulet device. LAAO is indicated for patients who are at risk of bleeding and who cannot tolerate long term oral anticoagulation. DS is a rare complication of the LAAO procedure with one study documenting a <1% incidence. Along with one case report highlighting DS as a complication post ligation of the left atrial appendage with a LARIAT suture. These were the only recorded associations found on literature review. The aim of this case report is to increase the awareness of DS as a potential complication to medical and surgical staff conducting LAAO in the process of improving patient care. Case Presentation: An 85 year old man with a history of ischaemic stroke, dyslipidaemia, gout and pernicious anaemia presented with a background of melena secondary to peptic ulcer disease (PUD) and epistaxis while on Apixaban 2.5mg twice daily oral anticoagulation for permanent atrial fibrillation. A successful procedure was carried out and the patient was recommenced on Apixaban 2.5mg twice daily for six weeks. Three weeks post procedure, the patient presented with fever, pleuritic chest pain and dyspnoea. On TOE, a significant pericardial effusion was noted. The pericardial effusion was monitored and was found to be increasing in size along with a deteriorating blood pressure of below 90 systolic. An emergent pericardiocentesis using the subxiphoid approach was performed. a further 24 hours with a follow up echocardiogram indicated. Investigations figure 1 - TOE demonstrates the LAAO device being inserted. Figures 2 and 3 show four week post procedure TOE highlights the new pericardial effusion with no rupture of the device in situ. Discussion: The patient was noted to suffer from the autoimmune condition pernicious anaemia. Autoimmune conditions are frequently encountered in tandem with each other, with one paper stating the a second autoimmune condition will be present in 25% of patients. While gout is not autoimmune, it is inflammatory. Chronic inflammation can similarly predispose a patient to dysfunction in the inflammatory response. It may be theorised that in this case, the patient was at a higher risk of developing a disease like DS given their clinical history. Conclusion: The association of DS as a complication post LAAO is exceptionally rare. Its uniqueness may be attributable to several causal factors including its ability to mimic more common conditions, along with its declining incidence via improved revascularisation techniques.